Frazni glagoli v slovenskem knjižnem jeziku 16. stoletja - Merše, Majda (Slavia Centralis, 2020)
Periphrastic Light-Verb Phrases in the 16th-Century Slovene Literary Language The 16th-Century Slovene literary language frequently includes phrases like dati odgovor/k odgovori ʻto give an answerʼ, delati greh ʻto commit a sinʼ, biti v skrbi ʻto be worriedʼ, i.e., the so-called periphrastic light-verb phrases (also called “expanded predicates”). The article examines the typology, semantic scope, and influence of translation on these phrases, which most commonly include semantically weakened verbs, such as the sample verbs biti ʻto beʼ, dati/dajati ʻto giveʼ, and delati ʻto do’. Other factors contributing to the variety in these phrases are differences in word formation, structure, and origin of the subject complement. The author also discusses their contextual (syntactically relevant) interchangeability with synonymous derived verbs (e.g., pričo dati – pričati ʻto give testimony’ vs. ‘to testify’).